Acute Ethanol Inhibits Dopamine Release in the Nucleus Accumbens via α6 Nicotinic Acetylcholine Receptors - Schilaty, Nathan D. (The American Society for Pharmacology and Experimental Therapeutics, 2014)
Electrophysiology and microdialysis studies have provided compelling evidence that moderate to high ethanol concentrations enhance dopamine (DA) neurotransmission in the nucleus accumbens (NAc) through the mesolimbic DA system. However, with fast-scan cyclic voltammetry, short-term exposure to moderate to high doses of ethanol decreases evoked DA release at terminals in the NAc. The aim of this study was to evaluate the involvement of nicotinic acetylcholine receptors (nAChRs) in modulating the effects of ethanol on DA release in the NAc of C57BL/6 mice ex vivo and in vivo. Local stimulation evoked robust, frequency-dependent DA release in the NAc slice preparation, with maximal release at 40 Hz in the shell and 20 Hz in the core. Nicotine decreased DA release in a concentration-dependent (0.01–10 μM) manner in the shell and core, with an IC(50) of 0.1 μM ex vivo and 0.5 mg/kg in vivo. Nicotine and ethanol inhibition of DA release was blocked by the α6*-nAChR antagonist α-conotoxins CtxMII and α-CtxMII [H9A; L15A] ex vivo (100 nM) in the core but not the shell. Furthermore, the nonspecific nAChR antagonist mecamylamine (2 mg/kg) blocked the effects of ethanol in the core in vivo. These findings suggest that DA release is inhibited by ethanol via nAChRs in the NAc and that DA modulation by nAChRs differs in the core versus the shell, with α6*-nAChRs affecting DA release in the core but not in the shell.